2015
DOI: 10.1007/s11547-015-0498-0
|View full text |Cite
|
Sign up to set email alerts
|

Transbrachial approach to the treatment of uterine leiomyomas with embolization of the uterine arteries: a preliminary technical experience

Abstract: In the treatment of symptomatic uterine fibromas, embolization of the uterine arteries performed via a transbrachial approach was shown to be safe and technically valid with regard to reducing the overall time of the intervention, ease of selective catheterisation, and shorter times spent in hospital, as well as being better accepted by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Pieri et al reported that in a series of 1490 varicoceles the percutaneous retrograde sclerotherapy via the basilic vein was successful in only 79.2% of cases because in the remaining patients, there was a venous spasm during the introduction of the cannula, particularly in children. 79 We found an overall rate of technical failure of 10.2% with the retrograde technique, often due to difficult cannulation of the internal spermatic vein via the femoral vein in 10-20% of patients. 67,68 Finally, it must be noted that both the antegrade and retrograde techniques expose patients to radiation (including the testicles).…”
Section: Therapeutic Advances In Urologymentioning
confidence: 83%
“…Pieri et al reported that in a series of 1490 varicoceles the percutaneous retrograde sclerotherapy via the basilic vein was successful in only 79.2% of cases because in the remaining patients, there was a venous spasm during the introduction of the cannula, particularly in children. 79 We found an overall rate of technical failure of 10.2% with the retrograde technique, often due to difficult cannulation of the internal spermatic vein via the femoral vein in 10-20% of patients. 67,68 Finally, it must be noted that both the antegrade and retrograde techniques expose patients to radiation (including the testicles).…”
Section: Therapeutic Advances In Urologymentioning
confidence: 83%
“…In a recent report, UAE performed via a brachial approach was shown to be safe and technically valid, with ease of selective catheterization and without the need of catheter exchanges. This also may be better accepted by patients due to early ambulation, avoidance of bladder catheterization, and also a lower radiation dose (5).…”
mentioning
confidence: 99%